PENGEMBANGAN SISTEM PENDANAAN REDD+ BERDASARKAN PEMBELAJARAN DARI MEKANISME PEMBAYARAN JASA LINGKUNGAN - Setiasih Irawanti; Aneka Prawesti Suka; Indartik Indartik; Fitri Nurfatriani; Nunung Parlinah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Seventy percent of Indonesia's land is forest area which has an opportunity for implementing Reducing Emissions from Deforestation and Forest Degradation+ (REDD+). Clean Development Mechanism (CDM) funding mechanism and the role of actors were analyzed using marketing chain approach (ILO, 2009), calculating the cost of CDM based on the cost of planting per hectare, estimated profitability using PresentValue (PV), and learning from payment of water services. TheCDMprogram funded by non-public grant from corporate social responsibility (CSR) for land rehabilitation conducted by farmer group on the land that unplanted for 30 years. The investors fasilitated by intermediary of farm administrator or non-government organizations without involving the government. Monitoring, reporting and verification (MRV) based on 10 years contract period, 1,000 stems per hectare in the 10 , and payment based on the success of plantation. Learning from the water service payments that payments mechanism from industries to farmers group conducted through intermediaries which operational costs from international agencies and local government budgets. Five year contract payment are equipped of legal documents, the 500 stems per hectare spreads across the land, farmers can harvest the other trees. For both mechanism, the farmers group fully follows the requirements set by the investors.